Contribution of Increases in Late Systolic Ejection Volume to the Impact of Heart Rate on Central Arterial Pulse Pressure in a Community Sample. (19th August 2022) - Mthembu, Nonhlanhla; Norton, Gavin R; Peterson, Vernice R; Naran, Ravi; Yusuf, Suraj M; Tade, Grace; Bello, Hamza; Bamaiyi, Adamu; Libhaber, Carlos D; Dessein, Patrick; Peters, Ferande; Sareli, Pinhas; et al.
Abstract: BACKGROUND: A lower heart rate (HR) increases left ventricular (LV) ejection volume. Whether this contributes to the adverse effects of HR on central pulse pressure (PPc) through reservoir volume effects is uncertain. METHODS: Using noninvasive central pressure, aortic velocity, and diameter measurements in the outflow tract (echocardiography), we assessed the role of LV ejection volume as a determinant of HR relations with PPc in 824 community participants. RESULTS: A lower HR was independently associated with both stroke volume (SV) ( P < 0.001) and a shift in ejection volume from early (until the first systolic shoulder) to late (from first systolic shoulder to peak PP) systole ( P < 0.05 to P < 0.005). Adjustments for LV end diastolic volume markedly diminished HR relations with SV and indexes of the shift in ejection volume to late systole. A lower HR was also independently associated with increases in forward traveling pressure waves (Pf) and PPc ( P < 0.0001). However, adjustments for neither SV, nor indexes of a shift in ejection volume to late systole modified HR-Pf or PPc relations. This was despite relationships between indexes of a shift in ejection volume to late systole and both Pf and PPc ( P < 0.0001). In contrast, adjustments for the increases in re-reflected and backward traveling wave pressures with a lower HR, eliminated HR-Pf and PPc relations. CONCLUSIONS: In contrast to current thought, a lower HR is not associated with increases in PPc through an impact of increases in late systolic ejection volume on aortic reservoir volume, but rather through increases in backward wave pressures. Graphical Abstract: